Tendencies in digital ethics research (overview analysis of modern research) - Maksat A. , Sadvokasov; Kulshat А. , Medeuova (BULLETIN of the L.N. Gumilyov Eurasian National University. Historical sciences. Philosophy. Religion Series, 2023)
The article presents discussions concerning the phenomenon of digital ethics. The terms, concepts, categories and criteria used in digital ethics are considered depending on the field of functioning – information ethics, computer ethics, and orthodox ethics. The cultural, social, industrial, philosophical and ethical aspects of the functioning of digital ethics are compared. A separate case concerning the impact of digital ethics on issues of interpersonal communication, including through the description of positive and negative scenarios for the use of digital ethics is considered. The genesis of previous, early, historical studies, approaches, ideas, concepts, somehow affecting ethical issues, especially digital ethics, is given. The resolution of contradictions between Western and Eastern ethical traditions applied to digital ethics has been carried out. The obstacles revealing the essence of the weak organization of ethical postulates are characterized. The need for a unified network of applied regulatory documents on digital ethics for the purposes of social well-being has been formalized and recognized. Various examples from the diverse layers of human life are given, allowing us to argue about the reference to digital ethics or ethics in general. The conclusion is made about the development of ethical concepts as a promising direction with significant evolutionary trends. A description of the methods, principles, and functions which the society can use for further research in this direction has been carried out.